2014
DOI: 10.1177/1934578x1400901117
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Honey from Marche, Central Italy: Classification of Unifloral and Multifloral Honeys by Multivariate Analysis

Abstract: The purpose of this study was the physicochemical characterization and classification of Italian honey from Marche Region with a chemometric approach. A total of 135 honeys of different botanical origins [acacia ( Robinia pseudoacacia L.), chestnut ( Castanea sativa), coriander ( Coriandrum sativum L.), lime ( Tilia spp.), sunflower ( Helianthus annuus L.), Metcalfa honeydew and multifloral honey] were considered. The average results of electrical conductivity (0.14 – 1.45 mS cm−1), pH (3.89 – 5.42), free acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
8
34
0
Order By: Relevance
“…But, at the ninth months of storage, statistically significant differences among HMF contents of honey samples stored in all containers ( p < .05). Truzzi et al () reported that the average results of electrical conductivity, pH, free acidity, and 5‐(hydroxy‐methyl)‐2‐furaldehyde of several honey types changed between 0.14 and 1.45 mS/cm, 3.89 and 5.42, 10.9 and 39.9 meq NaOH/kg, and 0.6 and 3.9 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…But, at the ninth months of storage, statistically significant differences among HMF contents of honey samples stored in all containers ( p < .05). Truzzi et al () reported that the average results of electrical conductivity, pH, free acidity, and 5‐(hydroxy‐methyl)‐2‐furaldehyde of several honey types changed between 0.14 and 1.45 mS/cm, 3.89 and 5.42, 10.9 and 39.9 meq NaOH/kg, and 0.6 and 3.9 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were classified, according to the regional chart of the Marche region edited in 2003 by Taffetani et al . (Lanari et al ., ; Truzzi et al ., ), as coming from Mid/Coastal Hilly belt or from High Hilly/Submountain belt and are reported in Fig. and Table where their production sites are shown as follows: samples are represented using the colours of the cluster groups described in Section 3.5.1.…”
Section: Methodsmentioning
confidence: 99%
“…In the Marche region, the production was around 1150 tons (Naldi, ) in 2012, and one of the most produced types was multifloral honey that contains a mixture of nectar and/or honeydew from different plant species (Osservatorio Nazionale Miele ). Usually, to enter the annual quality contest ‘Premio Qualità Miele Marchigiano’ sponsored by ASSAM (Agenzia per i Servizi nel Settore Agroalimentare delle Marche), the Marche agency for the agri‐food sector (ASSAM ), the multifloral honey is classified as coming from the Mid/Coastal Hilly belt (MCH) or from the High Hilly/Submountain (HHSM) belt (Lanari et al ., ; Truzzi et al ., ), on the basis of its production site. Consequently, it could be interesting to study if differences exist among these honeys according to their geographical origin to increase their commercial value, as it has already been performed for honeys from other countries (Di Marco et al ., ; Pocol et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the analytical evaluation of honey quality is very important to guarantee their quality and prevent the occurrence of adulterations. Several reports exist about the physicochemical composition of honeys from different countries and regions (Estevinho, Feás, Seijas, & Pilar Vázquez‐Tato, ; Mondragón‐Cortez, Ulloa, Rosas‐Ulloa, Rodríguez‐Rodríguez, & Resendiz Vázquezc, ; Silva et al., , Silva, Videira, Monteiro, Valentão, & Andrade, ; Silva, Alves, Das Fernandes, & Müller, ; Terrab, Recamales, Hernanz, & Heredia, ; Truzzi et al., ). Pollen analysis has become more popular in the recent times, once the consumers prefer monofloral instead of multifloral honeys.…”
Section: Introductionmentioning
confidence: 99%